ENRICHING MEDIA MERCHANDISE SARANA PENUNJANG PROMOSI STUDI KASUS PADA BOOKSTORE - Dewi Immaniar; Sudaryono Sudaryono; Ayu Ningrum (Universitas Raharja, 2014)
Talk about retail business can not be separated from the importance of service to consumers and good quality goods . But at the present time due to intense competition in the business world , the service and quality of goods is not enough to be able to increase revenue and attract customers loyal . This makes companies think hard to survive and stable in the business . One of them is by using a media campaign in this regard more toward print or visual media is indirectly felt the value of their effectiveness in communicating product marketing programs . PT . Times Prima Indonesia is a company engaged in the retail book with the name of the Times bookstores . Based on the analysis of the company’s problems requires additional media types supporting more varied and creatif promotion of existing ones, which will be used as a complement and a media campaign as well as to enrich the data renewal campaign design to capture the interest of consumers in which one form of the media campaign is shaped merchandise . Therefore , do Enriching ( enrich ) media campaign merchandise before it is less varied and has not formed a company image . The methodology used is the analysis, observation and design . Besides the new design has been tested with the implemented test duration for 6 months, and greatly increases the perceived contribution , this is evidenced by the chart sales increasing each month.